Socio-Economic Origins of Constitutional Review in Central Asia: Political Economy and Politico-Historical Context as Defining Factors - Saniia Toktogazieva (Constitutional Review, 2021)
This article pursues two main objectives. First, to identify the main factors behind the establishment of constitutional review in Central Asia. Second, to define how those factors have shaped the institutional design of constitutional courts. In doing so, this article revisits standard theories of comparative constitutional law in terms of the origin of judicial review. While the insurance theory dominates the present global discourse on judicial review, it cannot completely and accurately account for the origin of constitutional review in Central Asia. Rather, this article conveys that the main impetus and motivation behind the establishment of constitutional courts and their institutional designs has been the economic interests of Central Asian states, determined by the region’s political and historical context.